Implementasi Pembelajaran Pantun di Sekolah Dasar dengan Media Poketun Berbasis Android - Indra Nugrahayu Taufik; Diyas Puspandari (Universitas Negeri Padang, 2024)
This research examines the learning of pantun in elementary schools using Poketun media. The use of Poketun media can help students convey theory, examples, and steps for making pantun. Apart from that, Poketun media also provides entertainment for students during the learning interaction process. The research method used is development in producing Poketun media by validating the product. The implementation of Poketun media in this research has shown positive results, both for teachers and students. The results of the research show that the use of Poketun media as a medium for learning pantun in elementary schools is effective and efficient. This is proven by positive responses from students and teachers. They agreed that with Poketun, learning pantun in elementary schools would become more interesting. The use of Poketun media in learning pantun in elementary schools provides a different learning experience than usual. Students are given more flexible opportunities in space and time (situations and conditions). This trains students' creativity and independence so that they can develop further according to their potential interests and talents. The existence of Poketun media makes learning more interactive and can create expressive spaces in learning literature, especially Pantun, both online and offline in elementary schools.